Assessment of Rickshaw Pullers’ Knowledge, Attitude, and Safety Practices Regarding COVID-19 Infection: Rickshaw Pullers’ Knowledge, Attitude, and Safety Practices Regarding COVID-19 - Kiary, Rumpa; Nurunnabi, Mohammad; Hossain, Irin (Journal of the Medical College for Women & Hospital, 2025)
Background: The COVID-19 pandemic has prompted a comprehensive reevaluation of knowledge, attitudes and safety practices (KAsP) across diverse populations including rickshaw pullers. Aim: To assess the knowledge, attitude and safety practices regarding COVID-19 among rickshaw pullers.Materials and Method: A cross-sectional study was conducted among 187 rickshaw pullers in selected areas of Dhaka City from January to December 2020. Participants aged ≥18 years were conveniently sampled. Data were collected via face-to-face interviews using a pre-tested semi-structured questionnaire covering socio-demographics, COVID-19 knowledge, attitudes, and safety practices. Results: Most respondents revealed average levels of knowledge (45.5%) and safety practices (87.7%), but majority (94.1%) unveiled negative attitude. The level of knowledge was found to be statistically significantly associated with marital status, type of family, job loss due to the pandemic, and ownership of a homestead, with p≤0.05. Similarly, the level of practice showed significant associations with marital status, education, and monthly family income, with p≤0.05. The level of attitude was found to be statistically significantly associated with monthly family income, with p≤0.05. The correlations between knowledge, safety practices, and attitude regarding COVID-19 among rickshaw pullers findings indicate that a positive correlation exists between the level of knowledge and attitude (p≤0.05). Also a positive correlation was evident between attitude and knowledge levels (p≤0.05).Conclusion: The study revealed that majority of respondents had negative attitudes, while a significant number showed average levels of knowledge and safety practices. This study provided important insights for targeted interventions focused on improving rickshaw pullers' comprehension of COVID-19 safety measures. J Med Coll Women Hosp.2025; 21 (2):123-135